Incremental Concentrations of Tacrolimus Eye Drops as a Strategy for the Management of Severe Vernal Keratoconjunctivitis - Albarry, Maan Abdullah; Parekh, Mohit; Ferrari, Stefano; Eltahir, Heba Mahmoud; Shehata, Ahmed M; Shaker, Mohamed A; Elbadawy, Hossein Mostafa (Frontiers in Pharmacology, 2022)
Purpose: To assess the effect of different concentrations of tacrolimus eye suspension on the epithelium and stromal keratocytes of human corneas and investigate whether it can be safely used for severe cases of vernal keratoconjunctivitis (VKC). Methods: Tacrolimus eye suspension was prepared in a range of concentrations of 0.005%, 0.01%, 0.05%, 0.1%, and 0.2%. Molecular analysis was performed ex vivo on human corneas (n = 18), obtained from the eye bank. Transparency and thickness of each cornea were measured while live/dead staining was performed using a triple labeling assay. An incremental concentration approach was then tested on three severe cases of VKC. Results: All tested tacrolimus concentrations showed no significant changes in corneal thickness or transparency. In corneas treated with 0.1%, rare scattered dead cells were observed, while the folds of corneal surfaces were mostly viable, unlike concentrations higher than 0.1% and lower than 0.05%. Stromal cell densities were highest in the 0.1% tacrolimus treatment condition. Incremental concentrations of tacrolimus suspension were shown to significantly improve VKC cases, where the concentration used for each case depended on the severity of the case. Conclusions: Topical administration of tacrolimus was not toxic to human corneal cells at all tested concentrations, and the 0.1% concentration has shown the best viability of the corneal tissue. Tacrolimus eye suspension was shown to be safe and effective for use in severe VKC and is proposed as a topical ocular immunosuppressant drug enabling clinicians to incrementally increase the drug concentration according to the clinical severity of the disease to achieve the optimal therapeutic response.